2017
DOI: 10.3117/plantroot.11.70
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of plastic root responses to contiguous water gradient in rice

Abstract: Root plasticity is the key trait for plant adaptation to environmental stresses. To quantify phenotypic plasticity to its full extent in potential, it needs to be evaluated under contiguous environmental changes. For that purpose, we used the combination of chromosome segment substitution lines (Nipponbare/Kasalath CSSLs) and line source sprinkler (LSS) system of irrigation. For analysis, we first attempted to apply the coefficient of variation (CV) and norm of reaction that have been used as the conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…Previous studies have shown experimental evidences of genotypic variations in root plasticity expressed in response to heterogeneous soil environments for the adaptation of rice plants (Bañoc et al, 2000a;Siopongco et al, 2008;Kano-Nakata et al, 2013;2017;Kameoka et al, 2015;Menge et al, 2016;Niones et al, 2012;Nguyen et al, 2018;Owusu-Nketia et al, 2018;Suralta et al, 2010Suralta et al, , 2016Suralta et al, , 2018Tran et al, 2014). In this study, the CSSLs showed no significant differences in root system development with the recurrent parent under CWL in both experiments.…”
Section: Discussionsupporting
confidence: 45%
“…Previous studies have shown experimental evidences of genotypic variations in root plasticity expressed in response to heterogeneous soil environments for the adaptation of rice plants (Bañoc et al, 2000a;Siopongco et al, 2008;Kano-Nakata et al, 2013;2017;Kameoka et al, 2015;Menge et al, 2016;Niones et al, 2012;Nguyen et al, 2018;Owusu-Nketia et al, 2018;Suralta et al, 2010Suralta et al, , 2016Suralta et al, , 2018Tran et al, 2014). In this study, the CSSLs showed no significant differences in root system development with the recurrent parent under CWL in both experiments.…”
Section: Discussionsupporting
confidence: 45%
“…Three chromosome segment substitution lines from upland rice cultivar 'Kasalath' (CSSL45, 47 and 50) in the background of cultivar 'Nipponbare' were associated with increased shoot dry weight than the control when under water deficit conditions. This response indicated that plasticity in root system development enhanced water uptake ability in mildly droughted soil [13,27,28]. Similarly, plasticity in root system development of introgression lines (ILs) ILsYTH183 and IL-sYTH304 in shallow soil layers contributed to the greater shoot dry weight over that of the background cultivar IR64, with ILsYTH183 showing rapid increases in root elongation and branching when rewatered after drought, which contributed to its higher shoot dry matter production and water extraction compared to IR64 [29].…”
Section: Cultivated Germplasmmentioning
confidence: 95%
“…Trait standard deviation Trait mean 100 and norm reactions. In a set of chromosome segment substitution lines of rice grown under a continuous water gradient, the CV did not provide a good measure of root plasticity, but a non-linear curve of the reaction norm did [13]. Path analysis has been proposed for measuring plasticity resulting from selection [14].…”
Section: = − × Trait Plasticity Lowest Value Of Plant Trait Across Si...mentioning
confidence: 99%
“…Nipponbare and Kasalath are the parents of a set of Chromosome Segment Substition Lines (CSSLs). Using this set of CSSLs derived from a cross between Nipponbare and Kasalath, several studies have precisely quantified the root plasticity with minimal effects of genetic confounding (Kano-Nakata et al, 2011Kano-Nakata et al, 2017;Tran et al, 2014Tran et al, , 2015, as well as the detection of QTLs associated with root plasticity (Niones et al, 2013(Niones et al, , 2015. On the other hand, Sasanishiki and Habataki are the parents of another set of CSSLs (http://www.rgrc.dna.affrc.go.jp/ jp/).…”
Section: Plant Materialsmentioning
confidence: 99%